Overview of Adolescent Knowledge about Handling Dysmenorrhea - Fitri Nurhayati; Rd Noucie Septriliyana; Lina Haryani; Nanik Cahyati; Destiara Azzahra (CV. Get Press Indonesia, 2025)
Adolescent girls frequently experience dysmenorrhea, characterized by painful menstrual cramps that can disrupt daily routines, academic performance, and overall well‑being. Limited awareness of effective prevention and self‑care strategies often exacerbates the severity of symptoms, underscoring the need for comprehensive education on menstrual pain management. This study aims to determine the level of knowledge of adolescent girls about dysmenorrhea and its relationship with factors such as Body Mass Index (BMI), diet, menstrual duration, and menstrual cycle. Methods: This study used a quantitative descriptive design with a cross-sectional approach. A total of 85 female adolescent respondents were included in this study. Data were collected through questionnaires and analyzed in the form of frequency distribution. Results: The results showed that 67.1% of respondents had a sufficient level of knowledge about dysmenorrhea. A total of 25.9% of respondents experienced dysmenorrhea, and the majority of them had a sufficient level of knowledge. The majority of respondents had normal BMI (48.2%), a regular diet (71.8%), menstrual duration < 7 days (85.9%), and a regular menstrual cycle (70.6%), with most in each category showing a sufficient level of knowledge. Conclusion: Adolescent girls generally have a moderate level of knowledge about dysmenorrhea, which appears to be influenced by nutritional status, diet, and menstrual patterns. Improving reproductive health education can help enhance their ability to manage dysmenorrhea effectively.